Water Exposure and the Risk of Contact Lens–Related Disease. Issue 6 (June 2019) - Arshad, Memoona; Carnt, Nicole; Tan, Jacqueline; Ekkeshis, Irenie; Stapleton, Fiona
Abstract : Purpose: To describe the association of water exposure with contact lens (CL)–related disease and explore the guidelines regarding water exposure to CL wearers, provided by CL manufacturing industry, global public health, and CL–related professional associations. Methods: A review of the literature was conducted by searching PubMed, MEDLINE, and Web of Science databases up to September 2017 for articles published or translated in English using keywords: contact lens* AND tap water OR swimming OR showering OR water exposure AND microbial keratitis OR Acanthamoeba keratitis OR corneal infiltrate* OR ocular adverse event*. References in all relevant publications were also reviewed. Results: Water exposure during CL wear is associated with complications ranging from sterile corneal infiltrative events to sight-threatening infections. Despite the documented risks due to water exposure, water-related habits are common among CL wearers. This suggests a lack of awareness and understanding regarding the risks among CL wearers and potentially CL practitioners. Discrepancies exist in guidelines for CL hygiene and compliance provided by the CL manufacturing industry, global public health, and CL–related professional associations. There is also widespread use of water imagery within CL marketing and packaging materials. These factors may give rise to confusion among wearers and may contribute toward risk-taking behaviors. Conclusions: Consensus among stakeholders about water and CL care is needed. Guidelines should unequivocally advocate for the avoidance of any water exposure including handling CLs with wet hands, rinsing CLs or storage cases in tap water, showering while wearing CLs and swimming with CLs without wearing goggles. Abstract : Supplemental Digital Content is Available in the Text.